Impact of an acute care surgery service on timeliness of care at ramathibodi hospital - Chonlada Krutsri (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: An Acute Care Surgery [ACSx] service is composed of trauma, general surgical emergency cases, and surgical critical care patients, all of which has been introduced at Ramathibodi Hospital since August 1, 2015. Objective: To evaluate the outcome after one-year of services on the general surgical emergency patients’ flow from the emergency room [ER]. We collected data of pre-ACSx and post-ACSx periods to compared time to consultation, waiting time to OR, and resident satisfaction. Materials and Methods: A retrospective cohort was studied by collecting data to compare outcome of pre-ACSx and post-ACSx periods. Subgroup analysis was done by using Chi-square test and t-test. The resident satisfaction was evaluated by 12 residents using a double-blind questionnaire on http://www.surveycan.com/survey175782. Results: An ACSx service could improve flow of surgical emergency patients from the ER. From the present study, there were significant decreases in consultation time from 74.23 to 23.40 minutes (p-value <0.05) and in waiting time to operating room [OR] from 299.25 to 213.88 minutes (p-value <0.05). However, there was no statistical difference in the decrease of length of hospital stay (p-value 0.91). On subgroup analysis, there were significant decrease in consultation time in acute appendicitis, gut obstruction, acute cholecystitis, hollow viscus organ perforation, and hernia with complication (p-value <0.05). There was reduction in the acute appendicitis referral cases from 95 to 39 cases, and a reduction of ruptured rate from 45 to 13 cases. Resident satisfaction was more than 80% for ACSx service. Total complication and death were 18 cases (2.45%). Conclusion: Introduction of an ACSx service in the medical academic center, Ramathibodi Hospital had a good outcome in decrease of consultation time and waiting time to OR, significant in acute appendicitis cases. There were improved time of care and improved surgical emergency patients flow from ER with low complication and death rate (2.45%), with good satisfaction of more than 80% from residents.